Appcelerator titanium smartphone app development cookbook : over 80 recipes for creating native mobile applications specifically for iPhone and Android smartphones, no Ojective-C or Java required /: over 80 recipes for creating native mobile applications specifically for iPhone and Android smartphones, no Ojective-C or Java required. (©2011) - Unknown
No abstract available